Asthmatic athletes in the Italian team at Beijing 2008 Olympic Games - Todaro, A.; Egidi, F.; Sardella, F.; Di Cave, P.; Gramiccioni, C.; Bonini, M.; Padoa, S.; Pelliccia, A. (Medicina dello Sport, 2010)
Aim. The aim of the present study was to describe the clinical characteristics and, particularly, the spirometric findings in Italian asthmatic athletes taking part in the Beijing Olympic Games.